ASSESSMENT OF PERIODONTAL STATUS IN A GROUP OF PATIENTS AND CORRELATIONS WITH FACTORS WHICH FAVORING PERIODONTAL DISEASE - Cristina Vodiță; Emanuel Alin Vodiță; Costin Coman; Raluca Monica Comăneanu; Doina Lucia Ghergic; Laurența Lelia Mihai (Amaltea Medical Publishing House, 2021)
Objectives. The study aimed to assess the periodontal status of a group of patients and to highlight the correlations with factors favoring the occurrence and worsening of periodontal disease. Material and method. The study was carried out within the "Dr. Vodiță" Dental Clinic for a period of 2 years. The study group initially consisted of 266 patients who approached the Clinic for various dental reasons. We applied inclusion and exclusion criteria from the study to the initial group of patients. After applying the inclusion and exclusion criteria from the study, the final group of patients consisted of 205 patients of both sexes, aged between 18 and 76 years. The data were analyzed and statistically processed with the Microsoft Excel 2016 program. Results. The study group consisted of 138 male patients and 67 female patients, including 5 bruxomaniacs, 12 oral respirators, 36 patients with malocclusions and 54 patients with reduced or extended edentulous partially prosthetic. The Loe and Silness gingival index and the papillary bleeding index had the majority value 1. Discussions. In the present study, young patients were best represented. Cardiovascular diseases have an increased incidence among the group analyzed, 17.07% of patients said they live in stressful conditions and 47.32% of patients said they smoke. Conclusions. Most patients in the present study were young adults with generalized forms of periodontal disease. The main reasons for presenting to the doctor were gingival bleeding and halitosis, which are signs of periodontal disease. Smoking, daily stress and cardiovascular diseases are factors involved in the appearance and evolution of periodontal disease.